2019
DOI: 10.3390/v11030211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of A Novel Picorna-Like Virus, Burpengary Virus, that is Negatively Associated with Chlamydial Disease in the Koala

Abstract: Koalas (Phascolarctos cinereus) are native Australian marsupials whose populations are in decline from a range of threats. Infectious diseases caused by the bacterium Chlamydia pecorum and other pathogens are of particular concern. We analysed 26 poly-A selected RNA-sequencing libraries from a data set designed to study the immune response of koalas to ocular chlamydial infection. Using virus discovery techniques, we identified the coding-complete genome sequence of a novel picorna-like virus, denoted Burpenga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In addition, these phylogenies revealed a robustly supported relationship between chuvirus EVEs in the Tibetan frog (Nanorana parkeri) and zebrafish (Danio rerio) genomes. Taken together, these results provide evidence for the existence of numerous diverse lineages of chuviruses in vertebrates, adding to recent evidence for the presence of exogenous chuviruses in marsupials [64].…”
Section: Eves Derived From Viruses With Single-stranded Negative Sens...supporting
confidence: 75%
See 1 more Smart Citation
“…In addition, these phylogenies revealed a robustly supported relationship between chuvirus EVEs in the Tibetan frog (Nanorana parkeri) and zebrafish (Danio rerio) genomes. Taken together, these results provide evidence for the existence of numerous diverse lineages of chuviruses in vertebrates, adding to recent evidence for the presence of exogenous chuviruses in marsupials [64].…”
Section: Eves Derived From Viruses With Single-stranded Negative Sens...supporting
confidence: 75%
“…These issues, combined with rapid data accumulation, coverage limitations, and assembly errors-make generation of complete and accurate annotations difficult [83,85]. Consequently, labor-intensive manual genome annotation remains important [64,78], and most published whole genome are comprised of genomic "dark matter".…”
Section: Discussionmentioning
confidence: 99%
“…To date, metagenomic virus discovery studies have been conducted for several native and invasive species in Australia including rabbits, 36 foxes, 37 bats, 38 dasyurids (marsupial carnivores), 39 koalas 40 and shorebirds, 41 but expanding the number of species studied and the geographical range of these studies is needed to understand the dynamics of the Australian 'virome'. It is particularly important to conduct unbiased metagenomic screening of domestic species in frequent contact with humans, wildlife at the human-animal interface, and common invertebrate vectors of disease (e.g.…”
Section: The Threat Of Animal Reservoirs In Australiamentioning
confidence: 99%
“…This effect is not limited to insects. Harvey et al (2019) also found that presence of a novel picorna-like virus (Burpengary virus) is negatively associated with Chlamydial disease in the Koala (Harvey et al, 2019).…”
mentioning
confidence: 96%